2018 23rd International Conference on Engineering of Complex Computer Systems (ICECCS) 2018
DOI: 10.1109/iceccs2018.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Verification of Large-Scale Sensor Network Infrastructures

Abstract: Large-scale wireless sensor networks (WSN) are increasingly deployed and an open question is how they can support multiple applications. Networks and sensing devices are typically heterogeneous and evolving: topologies change, nodes drop in and out of the network, and devices are reconfigured. The key question we address is how to verify that application requirements are met, individually and collectively, and can continue to be met, in the context of large-scale, evolving network and device configurations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, bigraphs also admit a reactive theory that describes how they evolve over time. This can be used to allow runtime monitoring [17], where a single model is maintained by BigraphTalk and events, e.g. GUI updates, are passed from IoTtalk to trigger model updates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, bigraphs also admit a reactive theory that describes how they evolve over time. This can be used to allow runtime monitoring [17], where a single model is maintained by BigraphTalk and events, e.g. GUI updates, are passed from IoTtalk to trigger model updates.…”
Section: Discussionmentioning
confidence: 99%
“…The encoding mimics this separation of concerns using bigraph regions to split the model into a connection perspective, for checking forbidden configurations, and a typechecking perspective. Such a multi-perspective approach has proved useful elsewhere [17], [20] to increase the readability and ease of extension of models, as well as highlight potential design issues in the systems themselves.…”
Section: Modelling Iottalk With Bigraphsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sevegnani et al [10] demonstrated a modelling and verification framework of a large-scaled sensor network system. This framework is able to capture not only the spatial, operationalaspects but also the temporal evolution, which is the dynamic behaviour of the sensor network.…”
Section: Probabilistic Model Checkingmentioning
confidence: 99%